Effects of timing and duration of low voltage electrical stimulation of light and heavy carcasses on meat quality of South African feedlot cattle - Webb, E.C. (Edward Cottington) (University of Pretoria, 2019)
Thesis (PhD)--University of Pretoria, 2018.